2019
DOI: 10.4314/bcse.v33i1.17
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for determining the best process conditions for average Molecular weight and melt flow index of polypropylene

Abstract: The present work describes a mathematical model based on a population balance approach for determining the effect of the reaction temperature and hydrogen amount on the vital final product properties including average molecular weight and polydispersity index and flow index of polypropylene and also the profile rate of the polymerization. The aim of this study was to find the best operating condition through a model which is validated by the experimental data. The software program was coded in MATLAB/SIMULINK.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…(8) only validated in the absence of hydrogen with regarding this study circumstance, it would be suitable. In the presence of hydrogen, in the previous work [13], Eq. (8) is able to predict the melt flow index with a correlation coefficient (R 2 ) of 0.98.…”
Section: Mathematical Formulas and Equationsmentioning
confidence: 91%
See 3 more Smart Citations
“…(8) only validated in the absence of hydrogen with regarding this study circumstance, it would be suitable. In the presence of hydrogen, in the previous work [13], Eq. (8) is able to predict the melt flow index with a correlation coefficient (R 2 ) of 0.98.…”
Section: Mathematical Formulas and Equationsmentioning
confidence: 91%
“…In this study, the assumptions for modeling are: (1) It was supposed that propylene polymerization was carried out in the amorphous phase (2) the amorphous phase concentrations during polypropylene polymerization were at the thermodynamic equilibrium condition that obeys the one from Sanchez and Lacombe equation (SLE) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. 2It was assumed that γ1 = γ2 = ••• = γNC, where γ is equilibrium constant and NC are several solvents in slurry phase components [2].…”
Section: Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,13 The authors also found the best process conditions regarding the deactivation constant, 13,14 average molecular weight and melt flow index of the used catalyst. 15 They then decided to develop their model in order to cover the aforementioned gaps by proposing a validated mathematical model. This paper is a result of their decision.…”
Section: Introductionmentioning
confidence: 99%